3a+12=12a-3

Simple and best practice solution for 3a+12=12a-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a+12=12a-3 equation:


Simplifying
3a + 12 = 12a + -3

Reorder the terms:
12 + 3a = 12a + -3

Reorder the terms:
12 + 3a = -3 + 12a

Solving
12 + 3a = -3 + 12a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-12a' to each side of the equation.
12 + 3a + -12a = -3 + 12a + -12a

Combine like terms: 3a + -12a = -9a
12 + -9a = -3 + 12a + -12a

Combine like terms: 12a + -12a = 0
12 + -9a = -3 + 0
12 + -9a = -3

Add '-12' to each side of the equation.
12 + -12 + -9a = -3 + -12

Combine like terms: 12 + -12 = 0
0 + -9a = -3 + -12
-9a = -3 + -12

Combine like terms: -3 + -12 = -15
-9a = -15

Divide each side by '-9'.
a = 1.666666667

Simplifying
a = 1.666666667

See similar equations:

| 2ln*(x+1)-ln*(5x+1)+ln*(x-1)=ln*2 | | h(x)=4x^2-9 | | x+x-560x= | | 3x+(x-50)=180 | | 7e^9x=1071 | | 5x^2-33x=-18 | | 3y-9y=0 | | 1-16cos^2x=0 | | (X+5)+x=55 | | 13+2x=-39+12x | | -7(2t+7)=-35 | | x^3+4x^2=100*100*100 | | 6x-7+3x+5x-2=8 | | 5y-6=y-3+y | | -(c-10)=-118 | | 2x+25=4x-85 | | (3r+2)=0 | | 4+5=-8+x | | w-2y=7 | | 9-24=39 | | 3(2cos^2(x)-1)= | | 6w-10=2w+4 | | 3n+4=n+5*2 | | 5x+x=55 | | X+.0675X=300 | | 5y-3x-y+2x= | | k=(9s-5t)/4t | | 8*x-(1000/(x^2))=0 | | (-3u-7)(2u+7)=0 | | a/10-8=2 | | 5x+y=73 | | a/10-8= |

Equations solver categories